Political Narratives in the Middle East and North Africa Conceptions of Order and Perceptions of Instability - Mühlberger, Wolfgang; Alaranta, Toni (Perspectives on Development in the Middle East and North Africa (MENA) Region, 2020)
VIII, 187 p. 7 illus., 6 illus. in color.